Comparative study of three rosemary (Rosmarinus officinalis L.) clones during the growing season - Engel, R.; Hegedűs, A.; Bodor, Zs.; Heltmann-Tulok, M.; Stefanovits-Bányai, É. (International Journal of Horticultural Science, 2005)
The growth rate of three rosemary clones, `Harmat', 'Salem' and `Horvát', their essential oil content and its components as well as the total phenol content and total antioxidant capacity in their aqueous and ethanolic extracts were compaired. Total phenol content (determined by Folin-Ciocalteau reagent) and antioxidant power (FRAP-value) of aqueous and ethanolic rosemary extracts were measured by spectrophotometric method. The essential oil content was determined from drug by water-steam distillation. `Harmat' showed the most intensive growth through the vegetation period. The total antioxidant power of the ethanolic extracts from all the three clones was similar: a decrease was observed at the end of the season. In most cases more antioxidant compounds were dissolved in the aqueous extracts. The total quantity of phenolic compounds shows a good correlation with the potential extent of stress effects. The difference among the phenol contents of the various clones can be derived from the difference in their tolerance, because phenols have antioxidant effects contributing to protection against harmful impacts. Difference between the two extraction methods (aqueous and ethanolic) is due to the distinct solubility of compounds. Some other components, like essential oil compounds also possess antioxidant effect and in this way they may influence the antioxidant power of extracts.